PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA PT. PERKEBUNAN NUSANTARA VI (PERSERO) UNIT USAHA DANAU KEMBAR - Yulia Risa (JCH (Jurnal Cendekia Hukum), 2018)
As the act number 40, 2007, about limited Company which have been released as a subtitution of the Act Number 1, 1995, there are many criticals and resistance from businnessman based on article 74 about corpotate social responsibility and environment.the researcher uses emptical study of law approach. The sampling tecnique is non propbability sampling in the from of purpusive sampling tecnique. PT. Perkebunan Nusantra that represents state owned corportions (BUMN). The purpose of this study is to know the regulation and implementation of CSR in accordance with the mandate of law and corporation. Based on the research result, it can be concluded that the substance of Law Number 19, 2003 concerning State Owned Enterprises and Law Number 40,  2007 concerning the Company Limited has accommodated the principles of CSR implicitly in certain articles as the embodiment of Article 33 paragraph (3) and (4) of the 1945 Constitution. Law No. 18,  2004 on Plantation not a single article that regulates CSR but in the articles certain have referred to the concept of triple bottom line. With the normalization of these CSR principles, the nature of responsibility from voluntary transforms into mandatory in the form of moral obligations as well as juridical obligations.